Floating Vegetable Cultivation: A Sustainable Livelihood Strategy for Flood Prone Areas of Bangladesh (Global Journal of Human-Social Science, 2020)
During monsoon, most of the lands become flooded in the southern region of Bangladesh. Therefore, in submerged lands, farmers practice floating vegetable cultivation. The main focus of this study is to explore the advantages, probability, and sustainability of the floating agricultural practice in Nazirpur Upazila under the Pirojpur district of Bangladesh. For the survey, 120 cultivators were selected by using simple random sampling and based on both primary and secondary data. A semi-structured questionnaire, Focus Group Discussion (FGD), and Key Informant Interview (KII) have been adopted to collect primary data. This paper explores the outcome of floating vegetable cultivation in the flood-prone areas of Bangladesh when farmers have no other income opportunities. The findings of the study elicit that floating bed cultivation can help to increase income, reduce poverty, and generate self-employment opportunities in flood-affected areas.
Keywords: a sustainable strategy; floating vegetable cultivation; flooding; flood adaption practice